2013
DOI: 10.1103/physrevb.88.020406
|View full text |Cite
|
Sign up to set email alerts
|

Orbital-resolved spin model for thermal magnetization switching in rare-earth-based ferrimagnets

Abstract: The switching of rare-earth-based ferrimagnets triggered by thermal excitation is investigated on the basis of an atomistic spin model beyond the rigid-spin approximation, distinguishing magnetic moments due to electrons in d and f orbitals of the rare earth. It is shown that after excitation of the conduction electrons a transient ferromagneticlike state follows from a dissipationless spin dynamics where energy and angular momentum are distributed between the two sublattices. The final relaxation can then lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
132
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 30 publications
5
132
0
Order By: Relevance
“…The element-selective technique allowed us moreover to observe the element-specific dynamics of the so-called "all-optical switching" (AOS) [8] in GdFeCo alloys, finding that it unexpectedly proceeds through a transient ferromagneticlike state where the FeCo sublattice magnetization points in the same direction as that of the Gd sublattice before complete reversal [5,9]. Recent theoretical works supported the distinct demagnetization times observed experimentally [10][11][12] and their crucial role on the transient ferromagneticlike state. AOS has been also demonstrated for other rare-earth transition-metal ferrimagnetic alloys as TbFe [13], TbCo [14], TbFeCo [15], DyCo [16], HoFeCo [16], synthetic ferrimagnets [16][17][18], and very recently in the hard-magnetic ferromagnet FePt [19].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The element-selective technique allowed us moreover to observe the element-specific dynamics of the so-called "all-optical switching" (AOS) [8] in GdFeCo alloys, finding that it unexpectedly proceeds through a transient ferromagneticlike state where the FeCo sublattice magnetization points in the same direction as that of the Gd sublattice before complete reversal [5,9]. Recent theoretical works supported the distinct demagnetization times observed experimentally [10][11][12] and their crucial role on the transient ferromagneticlike state. AOS has been also demonstrated for other rare-earth transition-metal ferrimagnetic alloys as TbFe [13], TbCo [14], TbFeCo [15], DyCo [16], HoFeCo [16], synthetic ferrimagnets [16][17][18], and very recently in the hard-magnetic ferromagnet FePt [19].…”
Section: Introductionmentioning
confidence: 90%
“…Although the full theoretical explanation of the thermally driven AOS process is still a topic of debate [9,12,[20][21][22][23], the distinct demagnetization rates of each of the constituting elements has been suggested as the main driving mechanism * denise.hinzke@uni-konstanz.de for the AOS observed on antiferromagnetically coupled alloy [9,10,12]. These findings have highlighted the question how ultrafast demagnetization would proceed in ferromagnetically coupled two-sublattice materials such as permalloy (Py).…”
Section: Introductionmentioning
confidence: 99%
“…Here each sublattice is separately coupled to the same heat bath, although they could be coupled to different heath baths, such as electron and phonon heat baths as shown in Ref. 28 or the same sublattice can be coupled simultaneously to the two baths. 29 As a consequence of the different magnetization response of each sublattice, given by the intrinsic parameters, one sublattice can heat faster ("hot") than the other ("cold").…”
Section: Theoretical Description Of Ultrafast Magnetization Dynammentioning
confidence: 99%
“…Despite the still ongoing debate on the mechanism of ultrafast demagnetization it has been shown that spin dynamics simulations within the Landau-Lifshitz-Gilbert, Landau-Lifshitz-Bloch, or Landau-Lifshitz-Baryakhtar formulations [26][27][28][29] can be used to describe ultrafast laser-induced demagnetization in alloys when a sufficiently large and fast dissipation of spin angular momentum is assumed.…”
Section: Introductionmentioning
confidence: 99%